Fenomena Alam Sebagai Sumber Inspirasi Penciptaan Karya Seni Lukis - -, Sukirno (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
This paper is a report from the study of the creation of works of art with a source of ideas of natural phenomena. In the context of the creation of art, nature with all its elements are sometimes seen as a theme, sometimes seen as a motive, sometimes also as an object of study, or a source of inspiration of artists (Soedarso SP,: 2006:30). This paper is at once answered the purpose of creation studies conducted by the author, which explains: how the phenomenon of destruction of nature as a source of ideas placed the creation of works of art? And how the process of making paintings with natural phenomena as a source of ideas?Keywords: natural phenomenon, the source of the idea of creation, painting.